2016
DOI: 10.1002/aic.15433
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell‐nucleation mechanism in foam injection molding with gas‐counter pressure via mold visualization

Abstract: The mechanisms of cell nucleation and growth are investigated in foam injection molding (FIM) using gas-counter pressure (GCP). An in-situ mold visualization technique is employed. The application of GCP suppresses cell nucleation, and prevents the blowing agent from escaping during mold-filling. The inherent structural heterogeneity in the regular FIM can be improved because of the uniform cavity pressure when employing GCP. The cavity pressure profiles show much faster pressure-drop rates using GCP, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Within the study Polystyrene (PS) in combination with CO 2 were used. [53][54][55][56] The processing variables of injection speed, flow resistance of the gate, content of the blowing agent, melt flow rate and addition of talc were investigated. It was concluded that the injection speed and the resistance of the gate did not affect the resulting cell density whilst the dissolved gas content within the polymer melt affect cell density.…”
Section: Cell Structurementioning
confidence: 99%
“…Within the study Polystyrene (PS) in combination with CO 2 were used. [53][54][55][56] The processing variables of injection speed, flow resistance of the gate, content of the blowing agent, melt flow rate and addition of talc were investigated. It was concluded that the injection speed and the resistance of the gate did not affect the resulting cell density whilst the dissolved gas content within the polymer melt affect cell density.…”
Section: Cell Structurementioning
confidence: 99%
“…Therefore, in this process, the magnitude of the external force has a great influence on the melt pressure, that is, the higher the applied force, the greater the pressure of the polymer melt. When the external force is removed, the pressure drop rate increases, and the system quickly reaches the thermodynamic instability state, which leads to a rapid rise in cell number and a short time for cell stabilization, thus improving the efficiency of cell formation [ 32 , 33 ]. According to formula (1), with the increase in melt pressure, Δ G decreased obviously ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Except the above solutions, GCP technology 2628 has been proved to be an effective method to solve the gas mark defects of FIM parts. Wu et al.…”
Section: Introductionmentioning
confidence: 99%